Advancing Construction Practices: Innovations, Efficiency, and Safety in The Digital Era - Berawi, Mohammed Ali; Miraj, Perdana; Sari, Mustika (UI Scholars Hub, 2024)
In the ever-changing landscape of the construction industry, digital tools and procedures are a cornerstone of architectural and engineering practices. Building Information Modeling (BIM) and other computational design methodologies transform how projects are imagined, planned, and executed. These tools improve design precision while allowing real-time collaboration across different teams. As a result, adopting digital approaches is no longer an option but rather a requirement for remaining competitive in the construction industry. These innovative approaches provide an in-depth understanding of project complexities, drive design optimization, and contribute to resource management efficiency. Construction efficiency has also improved due to lean manufacturing processes and process optimization techniques. These approaches emphasize waste reduction, improved workflows, and increased productivity, which are critical to meeting project timelines and budgets. In this age of technology, combining lean methods with advanced software tools empowers project teams by allowing them to accomplish more with less effort and cultivating a culture of continuous improvement. By combining traditional lean strategies with current digital tools, the construction industry is setting new benchmarks for operational efficiency. Safety and stakeholder involvement are other important factors that benefit greatly from technology improvements in the construction industry. Enhanced safety measures, backed by digital technology, ensure that safety practices are strictly followed and monitored. Furthermore, digital platforms boost stakeholder engagement by giving all parties—from project managers and workers to investors and clients—access to real-time data and analytics. This transparency not only builds confidence but also guarantees that everyone engaged is aware of safety requirements and the progress of the project. This collaborative environment is critical for detecting potential risks early on and encouraging a proactive attitude to workplace safety. In addition to technological and methodological developments, the construction industry is becoming more focused on resilience and sustainability. Climate change and environmental sustainability require construction approaches that not only reduce environmental effects but also assure infrastructure resilience when unforeseen events occur. Sustainable practices are being integrated into project lifecycles to reduce carbon footprints, increase energy efficiency, and use environmentally friendly materials. Digital tools are critical in this effort, from optimizing resource consumption to allowing for the simulation of environmental implications during the design stage.